Defect Scheelite-Type Lanthanoid(III) Ortho-Oxomolybdates(VI) Ln0.667[MoO4] (Ln = Ce, Pr, Nd, and Sm) and Their Relationship to Zircon and the NaTl-Type Structure - Schustereit, Tanja; Müller, Sabine L.; Schleid, Thomas; Hartenbach, Ingo (Crystals (Basel), 2011)
The rare-earth metal(III) ortho-oxomolybdates with the formula Ln0.667[MoO4] (Ln = Ce, Pr, Nd, and Sm) and defect scheelite-type structure crystallize in the tetragonal space group I41/a (a = 533–525, c = 1183–1158 pm) with four formula units per unit cell. The Ln3+ cations at Wyckoff position 4b exhibit a coordination sphere of eight oxygen atoms in the shape of a trigonal dodecahedron. The same site symmetry (..) is observed for the tetrahedral oxomolybdate(VI) entities [MoO4]2–, since their central Mo6+ cation is situated at the 4a position. Due to this equal site multiplicity, the lanthanoid(III) cations have to be statistically under-occupied to maintain electroneutrality, thus a defect scheelite structure emerges. The partial structure of both the Ln3+ cations and the [MoO4]2– anions (if shrunk to their centers of gravity) can be best described as distorted diamond-like arrangements. Therefore, these two interpenetrating partial structures exhibit a similar setup as found in the zircon-type as well as in the NaTl-type structure.